1987
DOI: 10.1136/bmj.294.6570.487
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after surgical treatment of hidradenitis suppurativa.

Abstract: From six to 89 months after surgery 82 patients who had been treated by radical surgery (118 excisions) for intractable hidradenitis suppurativa were reviewed. Local recurrence rates varied greatly with the disease site, being low after axillary (3%) and perianal surgery (0%) and high after inguinoperineal (37%) and submammary (50%) excision. Recurrence results from inadequate excision or an unusually wide distribution ofapocrine glands, but physical factors such as obesity, local pressure, and skin maceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(59 citation statements)
references
References 19 publications
2
49
0
8
Order By: Relevance
“…Watson [139] noted the need for reoperation in approximately 20% of patients with inguinal disease whether they were treated with excision and primary closure or excision and skin grafting. Harrison et al [124] reported a 37% recurrence rate of inguinoperineal disease after wide excision without skin grafting. However, Ariyan and Krizek [140] and Thornton and Abcarian [141] recommended excision and secondary healing for patients with more extensive inguinoperineal and/or perianal-perineal disease, respectively, noting that the need for colostomy was rare.…”
Section: Reconstruction After Radical Wide Excisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watson [139] noted the need for reoperation in approximately 20% of patients with inguinal disease whether they were treated with excision and primary closure or excision and skin grafting. Harrison et al [124] reported a 37% recurrence rate of inguinoperineal disease after wide excision without skin grafting. However, Ariyan and Krizek [140] and Thornton and Abcarian [141] recommended excision and secondary healing for patients with more extensive inguinoperineal and/or perianal-perineal disease, respectively, noting that the need for colostomy was rare.…”
Section: Reconstruction After Radical Wide Excisionmentioning
confidence: 99%
“…When surgeons are uncertain about the extent of the disease, preoperative magnetic resonance imaging or ultrasound can be used. Alternatively, intraoperative color marking of sinus tracts with dyes such as methyl violet and iodine starch can be used to define the operative area [117,124,125]. …”
Section: Radical Wide Excisionmentioning
confidence: 99%
“…Da mit den regionären Lappenplastiken wiederum haartragende Haut, von der eine Neuerkrankung ausgehen kann, an die vormals erkrankte Stelle kommt, ist mit Rezidiven zu rechnen. Harrison et al [27] beobachteten aber auch ein Wiederauftreten nach radikaler Operation mit sekundärer Wundheilung. 6 Monate bis zu 7,5 Jahre nach Operation sahen sie in ihrem Kollektiv von 82 Patienten perianal keine, axillär in 5%, inguinal in 37% und submammär sogar in 50% der Fälle Rezidive.…”
Section: Therapieunclassified
“…First, its prevalence is still uncertain. It has been estimated to occur in a range from less than 0.1 [2-4] up to 2 [5], 4 [6], or even 8% [7]. Also, patients with HS have been treated by many different medical specialties, but by none of them in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients with HS have been treated by many different medical specialties, but by none of them in particular. This decentralization of care has resulted in a significant diagnostic delay of 5–14 years [7], causing an increased burden for the patients. Because of its comorbidities, including the metabolic syndrome, autoimmune diseases marked by systemic inflammation, such as Crohn’s disease, and the stigma and pain [8] that it causes, it has often been compared to psoriasis [9].…”
Section: Introductionmentioning
confidence: 99%